2019
DOI: 10.1016/j.aott.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Can capsular plication compensate the lack of one suture anchor in an arthroscopic three suture anchor Bankart repair? A comparative study

Abstract: ObjectiveThe aim of this study was to compare the complication rates and clinical results of labral repair with two suture anchors and capsular plication, and labral repair with three suture anchor fixation in artroscopic Bankart surgery.MethodsSixty-nine patients (60 males, 9 females; mean age: 28.2 ± 7.8 years (range: 16–50)) who had undergone arthroscopic repair of a labral Bankart lesion were evaluated. Group A underwent an arthroscopic Bankart repair with three knotless suture anchors, while group B under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…However, some studies have also reported that capsular plication does not lead to loss of external rotation. [8,31,32] In our study, there was no significant difference between the two groups after capsular plication and no significant external rotation loss was observed in any of the patients. [28] One of the main limitations of the present study is that the number of cases is relatively small.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…However, some studies have also reported that capsular plication does not lead to loss of external rotation. [8,31,32] In our study, there was no significant difference between the two groups after capsular plication and no significant external rotation loss was observed in any of the patients. [28] One of the main limitations of the present study is that the number of cases is relatively small.…”
Section: Discussionmentioning
confidence: 49%
“…[27] Similar biomechanical studies were conducted with single-loaded and double-loaded anchors. [10] Aydin et al [8] found that recurrence was higher in the group in which two knotless suture anchors were used. In this study, the authors found no significant difference between the two groups in terms of functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in delayed cases with repetitive dislocations, the anterior labrum is degenerated, which results in a lack of viable soft tissue to reconstruct the labral anatomy. In such cases, where labrum can't be repaired, the capsular plication is performed to restore stability [2].…”
Section: Introductionmentioning
confidence: 99%
“…The joint capsule and glenoid labrum are severely retracted in chronic cases with numerous recurrent dislocations, which results in insu cient viable soft tissue for capsular plication [2,3]. We have proposed that labral repair with Middle Glenohumeral ligament (MGHL) augmentation could be done to reconstruct anterior stability.…”
Section: Introductionmentioning
confidence: 99%